Recommendations to standardize preanalytical confounding factors in Alzheimer's and Parkinson's disease cerebrospinal fluid biomarkers: an update. (August 2012) - del Campo, Marta; Mollenhauer, Brit; Bertolotto, Antonio; Engelborghs, Sebastiaan; Hampel, Harald; Simonsen, Anja Hviid; Kapaki, Elisabeth; Kruse, Niels; Le Bastard, Nathalie; Lehmann, Sylvain; Molinuevo, Jose L; Parnetti, Lucilla; et al.
Early diagnosis of neurodegenerative disorders such as Alzheimer's (AD) or Parkinson's disease (PD) is needed to slow down or halt the disease at the earliest stage. Cerebrospinal fluid (CSF) biomarkers can be a good tool for early diagnosis. However, their use in clinical practice is challenging due to the high variability found between centers in the concentrations of both AD CSF biomarkers (Aβ42, total tau and phosphorylated tau) and PD CSF biomarker (α-synuclein). Such a variability has been partially attributed to different preanalytical procedures between laboratories, thus highlighting the need to establish standardized operating procedures. Here, we merge two previous consensus guidelines for preanalytical confounding factors in order to achieve one exhaustive guideline updated with new evidence for Aβ42, total tau and phosphorylated tau, and α-synuclein. The proposed standardized operating procedures are applicable not only to novel CSF biomarkers in AD and PD, but also to biomarkers for other neurodegenerative disorders.